The Use of "Particular Market Situation" Provision and its Implications for Regulation of Antidumping - Mikyung Yun (East Asian Economic Review (EAER), 2017)
The particular market situation provision of the WTO Antidumping Agreement is increasingly invoked against what may be described as "input-dumping," but this potentially violates the current Antidumping Agreement rules. This paper examines the practice and recent changes regarding the PMS provision in the US by critically examining relevant antidumping investigations in the US in light of GATT/WTO jurisprudence. Such US practice has not yet been extensively subjected to scholarly examination. The paper finds that the recent legal change in the US widens the scope and applicability of the PMS provision to cover input subsidies, allowing the use of not only surrogate prices but also surrogate costs. Further, the required standard of evidence to find PMS seems to have been diminished in the recent application. A widespread use of the PMS provision in such a deviant way calls for a fundamental review of the current trade remedy rules of the WTO.
Keywords: F13; F15; K33; 330; Particular Market Situation; PMS; Anti-dumping; Input-dumping; Input-subsidy